2020
DOI: 10.1002/ps.6105
|View full text |Cite
|
Sign up to set email alerts
|

Cyst nematode bio‐communication with plants: implications for novel management approaches

Abstract: Bio‐communication occurs when living organisms interact with each other, facilitated by the exchange of signals including visual, auditory, tactile and chemical. The most common form of bio‐communication between organisms is mediated by chemical signals, commonly referred to as ‘semiochemicals’, and it involves an emitter releasing the chemical signal that is detected by a receiver leading to a phenotypic response in the latter organism. The quality and quantity of the chemical signal released may be influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…The possible association between DE-lncRNAs and the pectin lyase-like superfamily protein as a pectin-degrading enzyme suggests pectin lyase-like superfamily gene/DE-lncRNA interaction-mediated defense signals via modification of cell wall integrity and lignin content, which is consistent with the obtained results in previous studies (Gallego-Giraldo et al, 2020). UDP-Dgalactose 4-epimerase5 which confers resistance to the cyst nematode Heterodera schachtii (Wubben et al, 2004), PIP and WOX which turned out to be involved, respectively, in auxindependent cell elongation and modulating developmental pathways after pathogen attachment (Maure et al, 2008;Olmo et al, 2020), the ABC transporter family gene which participates in the inhibition of hatch and repulsion of potato cyst nematodes (Globodera pallida and G. rostochiensis) through modulating root composition (Ochola et al, 2021), EXPs as cell wall-modifying genes functioning in host defense suppression (Ali et al, 2015;Samalova et al, 2020), and ANNAT8 and histidine kinase demonstrated to be altered by nematodes for feeding site formation (Dowd et al, 2017;Zhao et al, 2019) were the most important nematode-responsive genes which showed the potential relationship with DE-lncRNAs identified in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The possible association between DE-lncRNAs and the pectin lyase-like superfamily protein as a pectin-degrading enzyme suggests pectin lyase-like superfamily gene/DE-lncRNA interaction-mediated defense signals via modification of cell wall integrity and lignin content, which is consistent with the obtained results in previous studies (Gallego-Giraldo et al, 2020). UDP-Dgalactose 4-epimerase5 which confers resistance to the cyst nematode Heterodera schachtii (Wubben et al, 2004), PIP and WOX which turned out to be involved, respectively, in auxindependent cell elongation and modulating developmental pathways after pathogen attachment (Maure et al, 2008;Olmo et al, 2020), the ABC transporter family gene which participates in the inhibition of hatch and repulsion of potato cyst nematodes (Globodera pallida and G. rostochiensis) through modulating root composition (Ochola et al, 2021), EXPs as cell wall-modifying genes functioning in host defense suppression (Ali et al, 2015;Samalova et al, 2020), and ANNAT8 and histidine kinase demonstrated to be altered by nematodes for feeding site formation (Dowd et al, 2017;Zhao et al, 2019) were the most important nematode-responsive genes which showed the potential relationship with DE-lncRNAs identified in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Cyst nematodes (Heteroderidae; Globodera rostochiens ) is causing a loss of approximately US $125 billion annually worldwide, as major root parasitic nematodes ( Chitwood, 2003 , Fouda et al, 2020 , Kumar et al, 2021 , Ochola et al, 2021 ). Crops, such as wheat, soybean, potato, and rice, have been destroyed because of cyst nematode species.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used free eggs artificially removed from cysts for hatching assays, and our result clearly demonstrated that SEB can induce the hatching of J2 in eggs. The interior of a cyst is a hatching-suppressive environment because of the influence of cyst contents and cyst wall-derived compounds (33)(34)(35). Cysts also act as a physical barrier to chemicals.…”
Section: Discussionmentioning
confidence: 99%